Meningkatkan Mutu Belajar Siswa SMP NU An Naashiri Pasrujambe Dalam Masa PPKM - Asisahtul Khasanah Bilah; fadhil akbar (LP3M IAIFA Kediri, 2021)
Learning is defined as the process of behavior change as a result of an individual's interaction with his environment. Teachers are one of the factors that determine the success of the learning process. The learning process must be supported by adequate learning facilities or learning media and supported by the ability and skills of teachers in the implementation of learning. This research uses a descriptive qualitative approach because it is suitable for use to gain an in-depth understanding of social phenomena. The purpose of this study is to find out (1) the improvement of the quality of student learning during ppkm (2) the impact of improving the quality of learning in the PPKM (3) barriers to improving the quality of learning in the PPKM period.